2001
DOI: 10.3104/reports.109
|View full text |Cite
|
Sign up to set email alerts
|

The linguistic and cognitive profile of Down syndrome: Evidence from a comparison with fragile X syndrome

Abstract: -In this paper, we report on the results of our research, which is designed to address two broad questions about the cognitive and linguistic profi le of Down syndrome: (1) Which domains of functioning are especially impaired in individuals with Down syndrome? and (2) Which aspects of the language and cognitive profi le of Down syndrome are syndrome specifi c? To address these questions, we focused on three dimensions of the Down syndrome profi le -receptive language, expressive language, and theory of mind -a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 19 publications
7
77
0
5
Order By: Relevance
“…While Baron-Cohen et al (1985) found that 85% of a group of children with DS could pass a standard first-order false belief task of ToM, Charman and Campbell (1997) reported that 39% of a sample of children with DS passes false belief tasks. Abbeduto et al (2001) found that the participants with DS, as a group, answered substantially fewer false beliefs questions correctly than did typically developing (TD) participants.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…While Baron-Cohen et al (1985) found that 85% of a group of children with DS could pass a standard first-order false belief task of ToM, Charman and Campbell (1997) reported that 39% of a sample of children with DS passes false belief tasks. Abbeduto et al (2001) found that the participants with DS, as a group, answered substantially fewer false beliefs questions correctly than did typically developing (TD) participants.…”
Section: Introductionmentioning
confidence: 93%
“…The aim of such tasks is to assess the ability of the participant to reason about another person's beliefs when those beliefs are different from his or her own. There have been hundreds of articles concerning these tasks, comparing the performance of different groups, of the same mental age (MA) or chronological age (CA), exploring how success correlates with linguistic and general cognitive and social skills, and extending the task in various ways (Abbeduto et al, 2001;Tager-Flusberg & Sullivan, 1994;Yirmiya et al, 1998). To date, only a few investigators have explored ToM abilities in children with DS (Cornish et al, 2005;Zelazo et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Relative strengths in Down syndrome may be in the areas of implicit memory (Carlesimo, Marotta & Vicari, 1997;Vicari, 2001;Vicari, Bellucci & Carlesimo, 2000) and visual-motor processing (Silverstein, Legutki, Friedman & Takayama, 1982;see Wang, 1996). Relative weaknesses are in language processing (Abbeduto, 2001;Chapman, 1995;2001;Fowler, Gelman & Gleitman, 1994) and in working memory (Jarrold & Baddeley, 2001;Marcell & Weeks, 1988;McDade & Adler, 1980). The present paper is concerned with the relative weakness in working memory and prospects for ameliorating it.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggested youth with DS have smaller brains resulting in part from reduced prefrontal cortex volume (Jernigan, Bellugi, Sowell, & Doherty, 1993;Pinter, Eliez, Schmitt, Capone, & Reiss, 2001). The prefrontal cortex has long been associated with higher-order cognitive processing, and consequently, it has been well established that youth with DS experience particular deficits in executive functioning and language (Lanfranchi, Jerman, Dal Pont, Alberti, & Vianello, 2010;Abbeduto et al, 2001). Because of abnormal prefrontal cortexes, as well as abnormal corpus colossal regions (Wang, Doherty, Hesselink, & Bellugi, 1992), researchers have additionally speculated that youth with DS may experience insufficient sustained attention.…”
Section: Introductionmentioning
confidence: 99%